Is it time to retire `talent` from discussions of athlete development? - Baker, J.; Johnston, K.; Till, K. (High Ability Studies, 2023)
The word "talent" is used across many sport disciplines - to describe an athlete`s prowess (i.e. "he is talented"), as a term for what is sought after during assessment and selection (i.e. talent selection camps) or in reference to players to be developed (i.e. "a group of talents"). While the term has received research attention regarding its definition and criteria, its utility in practical settings is often debated. In this paper, we review several areas of concern researchers have raised for using the term "talent" and why this matters in the context of athlete development. While the notion of talent continues to resonate with coaches, scientists and practitioners, we suggest several areas for future research and recommendations for the use of this controversial term.